(a²-b²)³+(b²-c²)³+(c²-a²)³/(a-b)³+(b-c)³+(c-a)³
Answers
Answered by
3
Answer:
As we know if A + B + C = 0 then A³ + B³ + C³ = 3ABC
Here in numerator
A = a² — b²
B = b² — c²
C = c² — a²
and A + B + C = a² — b² + b² — c² + c² — a² = 0
So,(a²-b²)³ + (b²-c²)³ + (c²-a²)³ = 3(a²-b²)(b²-c²)(c²-a²)
And now in denominator
A = a — b
B = b — c
C = c — a
and A + B + C = a — b + b — c + c—a = 0
So,(a-b)³ + (b-c)³ + (c-a)³ = 3(a-b)(b-c)(c-a)
Hence,
(a²-b²)³ + (b²-c²)³ + (c²-a²)³ / (a-b)³ + (b-c)³ + (c-a)³
= 3(a²-b²)(b²-c²)(c²-a²) / 3(a-b)(b-c)(c-a)
= (a+b)(b+c)(c+a)
Step-by-step explanation:
Please mark as brainliest answer and follow me please and thank me please Because I am a very good boy
Answered by
0
Answer:
answer is
(a+b) (b+c)(c+a)
Similar questions